Left ventricular end-diastolic pressure is associated with left atrial functional measures by echocardiography. (8th February 2021) - Olsen, FJ; Mogelvang, R; De Knegt, MC; Galatius, S; Pedersen, S; Modin, D; Ravnkilde, K; Gislason, G; Biering-Sorensen, T
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): The Danish Heart Foundation Background Assessment of maximal LA volume (LAVmax) is recommended in imaging guidelines but evidence suggests additional value of functional LA measures. How extended measures of LA function associate to left ventricular filling pressure has not been fully explored. Purpose To investigate the association between functional LA measures and left ventricular end-diastolic pressure (LVEDP) Methods Patients suspected of coronary artery disease referred for angiography had simultaneous left heart catheterization performed for invasive pressure measurements. LVEDP > 12mmHg was considered elevated. LA measurements by echocardiography included: LAVmax, minimal LA volume (LAVmin), total LA emptying fraction (total LAEF), passive LA emptying fraction (passive LAEF), and active LA emptying fraction (active LAEF). Results Of 43 patients, 28 (65%) had elevated LVEDP. These patients more frequently had coronary vessel disease (VD) and impaired LA mechanics by all accounts except by LAVmax. All LA measures except LAVmax were associated with LVEDP in unadjusted linear regression analyses, however, only LA emptying fractions remained associated with LVEDP after adjusting for age and VD (2.6 (1.2-4.0) mmHg increase, p = 0.001, per 5% decrease in total LAEF; 1.4 (0.1-2.8) mmHg increase, p = 0.040, per 5% decrease in active LAEF; 1.8 (0.1-3.4) mmHg increase, p = 0.038, per 5% decrease in passive LAEF). In logistic regression, passive LAEF was significantly associated with elevated LVEDP (figure), and this was also the case after adjusting for age and VD (OR = 1.11 (1.01-1.21), p = 0.023, per 1% decrease). Similar findings were made in subgroup analyses among patients without dilated LA and patients without conventional indicators of elevated filling pressure. Conclusion: Left ventricular end-diastolic pressure is significantly associated with LA functional measures but not LA volumes. Additionally, passive LAEF is associated with elevated LVEDP. Future studies examining LA function should include all components of LAEF.